Growth capital flows and volatility in the Trinidad and Tobago economy, 1970-2000 - Ramsaran, Ramesh ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2001)
Examines the performance of the economy in recent decades and gauges the impact of foreign capital on selected variables and on the functioning of the economy.